3D printing of crack-free high strength Zr-based bulk metallic glass composite by selective laser melting. (November 2017) - Ouyang, Di; Li, Ning; Xing, Wei; Zhang, Jianji; Liu, Lin
Abstract: 3D printing of crack-free bulk metallic glasses remains challenge due to the generation of huge thermal stress during the selective laser melting and their intrinsic brittleness. Herein, Zr55 Cu30 Ni5 Al10 system was selected and 3D printed by selective laser melting technique. The results indicated that bulk metallic glassy composite comprises a large fraction (about 83%) of amorphous phase and minor fraction of intermetallic compounds with free of cracks were successfully fabricated. The 3D printed metallic glassy composite exhibited high strength over 1500 MPa. Experiment combined with finite-element-method simulation not only revealed the mechanism of crystallization at heat affected zones, but demonstrated that low thermal stress reduce the risk of micro-cracks generation and fracture toughness plays a crucial role in suppression the crack propagation during selective laser melting process. Highlights: A crack-free Zr-based bulk metallic glass composite was successfully fabricated by selected laser melting. The composite exhibited high strength of about 1500 MPa. Both low thermal stress and high fractural toughness responsible for the crack-free BMG composite in selected laser melting.